Women in society : Japan - Kanematsu, Elizabeth, 1959- (Singapore : Time Editions Pte Ltd, 1993)
Examines the experiences of women in Japanese society, discussing their participation in various fields and profiling the lives of significant women.
Includes bibliographical references (p. 127) and index.
Keywords: Women -- Japan -- Social conditions -- Juvenile literature